Answer:
![x=(5+√(19))/(2)\text{ and } x=(5-√(19))/(2)](https://img.qammunity.org/2021/formulas/mathematics/high-school/j2ar95mgi9v1g9c1ntol2s1l570isbtq73.png)
Explanation:
If we have the standard form
, then we can use the quadratic formula:
![x=(-b\pm√(b^2-4ac))/(2a)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/g0ca7qogjzpe8ajn601can4liohtrxutl2.png)
First, let's identify our coefficients. We have
.
This can be rewritten as
.
Therefore, a=2, b=-10, and c=3.
Substitute these values into the quadratic formula. This yields:
![x=(-(-10)\pm√((-10)^2-4(2)(3)))/(2(2))](https://img.qammunity.org/2021/formulas/mathematics/high-school/z4kyj3bq6bgy7eba69yskgq6mjkkpi9n2k.png)
From here, simplify. Evaluate the expression under the square root:
![x=(10\pm√(100-24))/(4)](https://img.qammunity.org/2021/formulas/mathematics/high-school/jys97i036r9wiwbw32c487lm2sr1q61k30.png)
Evaluate:
![x=(10\pm√(76))/(4)](https://img.qammunity.org/2021/formulas/mathematics/high-school/v7aq2fnsx4tiifh3swpd57l020qczree92.png)
Note that:
![√(76)=√(4\cdot 19)=√(4)\cdot√(19)=2√(19)](https://img.qammunity.org/2021/formulas/mathematics/high-school/5coxjifd0wg7n8fjbcy4q1kzkizlkyuht2.png)
Therefore:
![x=(10\pm2√(19))/(4)](https://img.qammunity.org/2021/formulas/mathematics/high-school/vdr19919w8qxc5mh9larnwq8yahrgnyhsu.png)
We can factor out a 2 from both the numerator and the denominator:
![x=(2(5\pm√(19)))/(2(2))](https://img.qammunity.org/2021/formulas/mathematics/high-school/m3v6c4kbstgbt7l6isrpphvstpl8t01op3.png)
Simplify:
![x=(5\pm√(19))/(2)](https://img.qammunity.org/2021/formulas/mathematics/high-school/8ljf36plaapn3gv2j76qjt6tdb7rkiy2b3.png)
Therefore, our roots are:
![x=(5+√(19))/(2)\text{ and } x=(5-√(19))/(2)](https://img.qammunity.org/2021/formulas/mathematics/high-school/j2ar95mgi9v1g9c1ntol2s1l570isbtq73.png)